Effect of the Vapour-Solution Interface Area on a Miniature Lithium-Bromide/Water Absorption Refrigeration System Equipped with an Adiabatic Absorber. (August 2017) - Osta-Omar, Salem M.; Micallef, Christopher
Abstract: Developments in electronics brought about increasing power densities where passive cooling is insufficient to keep components within acceptable temperature limits. This rapid development reflected in increasing interest in small capacity cooling systems. This study focuses on alternative technology and new methodology to design small capacity LiBr/water absorption refrigeration systems using refrigerant that is non-harmful to the environment. The main aim of this paper is to investigate and optimize the vapour-solution interface area (Ai ) in a miniature lithium-bromide/water (LiBr/water) absorption refrigeration system equipped with an adiabatic absorber for specific absorption rates in the adiabatic absorber. A new flow configuration of the LiBr/water solution inside the adiabatic absorber, using a horizontal spiral groove made of perspex plate was created for this purpose. This new configuration made it possible to control Ai while keeping the thickness of the LiBr/water solution inside the adiabatic absorber constant throughout the testing period. As a result, the effect of the solution thickness on the absorption rate could be eliminated and thus the effect of the vapour-solution interface area alone on the absorption rate could be investigated. This led to determine experimentally the optimal vapour-solution interface area inside the adiabatic absorber and found to be equal to 140 cm² for a 45 W cooling system.